Health Risk Characterization for Resident Inhalation Exposure to Particle-Bound Halogenated Flame Retardants in a Typical E-Waste Recycling Zone - Luo, Pei; Bao, Lian-Jun; Wu, Feng-Chang; Li, Shao-Meng; Zeng, Eddy Y. (ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2014)
Inhalation of pollutants is an important exposure route for causing human health hazards, and inhalation exposure assessment must take into account particle size distribution because particle-bound pollutants are size-dependent. Such information is scarce, particularly for residents dwelling within e-waste recycling zones where abundant atmospheric halogenated flame retardants (HFRs) commonly used in electronic/electrical devices have been widely reported. Atmospheric size-fractioned particle samples were collected using a 10-stage Micro-Orifice Uniform Deposit Impactor from an e-waste recycling zone in South China. The deposition efficiencies and fluxes of size-fractioned HFRs including polybrominated diphenyl ethers (PBDEs), alternative brominated flame retardants, and Dechlorane Plus in the human respiratory tract were estimated using the International Commission on Radiological Protection deposition model. The majority of HFRs was found to deposit in the head airways, with coarse particles (aerodynamic diameter (Dp) > 1.8 mu m) contributing the most (69-91%). Conversely, fine particles (Dp < 1.8 mu m) were dominant in the alveolar region (62-80%). The inhalation intake of PBDEs Within the e-waste recycling zone was 44 ng/d (95% confidence interval (CI): 30-65 ng/d), close to those through food consumption in non-e-waste recycling regions. The estimated total hazard quotient of particle-bound HFRs was 5.6 x 10(-4) (95% Cl: 3.8 x 10(-4)-8.8 x 10(-4)). In addition, incremental lifetime cancer risk induced by BDE-209 was 1.36 x 10(-10) (95% Cl: 7.3 x 10(-11)-2.3 x 10(-10)), much lower than the Safe Acceptable Range (1.0 x 10(-6)-1.0 x 10(-4)) established by the United States Environmental Protection Agency. These results indicate that the potential health risk from inhalation exposure to particle-bound HFRs for residents dwelling in the e-waste recycling zone was low.